2018
DOI: 10.1177/0961000618792367
|View full text |Cite
|
Sign up to set email alerts
|

One hundred tweets from library land: A case study of RMIT University Library (academic library) and State Library of Victoria (public state library) in Australia

Abstract: Twitter is used by different library types to communicate and engage with their community. This case study focuses on content choices in tweets and the level of engagement generated, in the context of two different types of library. The current study attempts to examine the contents of Library Twitter account of two libraries (academic and public) with the aim of evaluating in a comparative mode, their themes and levels of user engagement. This research used a mixed method research approach. For quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…As the type of posts is more crucial than the number of posts for attracting users' attention (Smeaton and Davis, 2014), participants were asked to demonstrate the content of their library's posts. Results (Table 7)in line with prior studies (Alsuhaibani, 2020;Bacon, 2017;Joo et al, 2018;Mahmood and Richardson, 2011;Taylor and Francis Group, 2014) revealed that libraries mainly use social media for communicating general announcements regarding library operations (88.1%), information about library events (85.8%) and event photos or videos (82.1%), as well as for promoting their services (80.6%). Librarians are also concerned about their communities' interests (58.2%), whereas news and/or information about Library and Information Science (25.4%) are shared to a smaller extent.…”
Section: Data Analysis and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As the type of posts is more crucial than the number of posts for attracting users' attention (Smeaton and Davis, 2014), participants were asked to demonstrate the content of their library's posts. Results (Table 7)in line with prior studies (Alsuhaibani, 2020;Bacon, 2017;Joo et al, 2018;Mahmood and Richardson, 2011;Taylor and Francis Group, 2014) revealed that libraries mainly use social media for communicating general announcements regarding library operations (88.1%), information about library events (85.8%) and event photos or videos (82.1%), as well as for promoting their services (80.6%). Librarians are also concerned about their communities' interests (58.2%), whereas news and/or information about Library and Information Science (25.4%) are shared to a smaller extent.…”
Section: Data Analysis and Discussionsupporting
confidence: 83%
“…and posts about collection (new arrivals) and events. By contrast, tweets of an academic and a public library in Australiarelated to services, events and collection promotionreceived more user engagement than the other types of tweets (Alsuhaibani, 2020). The aforementioned study also revealed that the content of tweets of the two libraries were different, customized to address different audiences.…”
Section: Social Media Use In Librariesmentioning
confidence: 93%
See 1 more Smart Citation
“…Π—Π° послСдниС дСсятилСтия ΠΈΠ½Ρ‚Π΅Ρ€Π½Π΅Ρ‚ ΠΏΡ€ΠΎΡ‡Π½ΠΎ закрСпился ΠΊΠ°ΠΊ срСдство ΠΊΠΎΠΌΠΌΡƒΠ½ΠΈΠΊΠ°Ρ†ΠΈΠΈ, получСния новостСй ΠΈ развлСчСния 1 (Π ΠΈΠ½Ρ‡ΠΈΠ½ΠΎΠ²Π°, 2020). ΠŸΡ€ΠΈ этом Π·Π½Π°Ρ‡ΠΈΡ‚Π΅Π»ΡŒΠ½Π°Ρ доля ΠΊΠΎΠΌΠΌΡƒΠ½ΠΈΠΊΠ°Ρ‚ΠΈΠ²Π½Ρ‹Ρ… ΠΈ Ρ€Π°Π·Π²Π»Π΅ΠΊΠ°Ρ‚Π΅Π»ΡŒΠ½Ρ‹Ρ… процСссов приходится Π½Π° ΡΠΎΡ†ΠΈΠ°Π»ΡŒΠ½Ρ‹Π΅ сСти, ΠΏΡ€Π΅Π΄ΡΡ‚Π°Π²Π»ΡΡŽΡ‰ΠΈΠ΅ ΠΈΠ· сСбя: 1) ΠΏΠ»Π°Ρ‚Ρ„ΠΎΡ€ΠΌΡƒ, Π½Π° ΠΊΠΎΡ‚ΠΎΡ€ΠΎΠΉ частныС Π»ΠΈΡ†Π° ΠΈ ΠΎΡ€Π³Π°Π½ΠΈΠ·Π°Ρ†ΠΈΠΈ ΠΌΠΎΠ³ΡƒΡ‚ ΡΡ‚Ρ€ΠΎΠΈΡ‚ΡŒ ΡΠΎΡ†ΠΈΠ°Π»ΡŒΠ½Ρ‹Π΅ ΠΎΡ‚Π½ΠΎΡˆΠ΅Π½ΠΈΡ ΠΌΠ΅ΠΆΠ΄Ρƒ Π΅Π΄ΠΈΠ½ΠΎΠΌΡ‹ΡˆΠ»Π΅Π½Π½ΠΈΠΊΠ°ΠΌΠΈ, Ρ€Π°Π·Π΄Π΅Π»ΡΡŽΡ‰ΠΈΠΌΠΈ ΠΎΠ΄Π½ΠΈ ΠΈ Ρ‚Π΅ ΠΆΠ΅ интСрСсы ΠΈΠ»ΠΈ Ρ†Π΅Π»ΠΈ, Π΄Π΅ΡΡ‚Π΅Π»ΡŒΠ½ΠΎΡΡ‚ΡŒ ΠΈ Π»ΠΈΡ‡Π½Ρ‹Π΅ Π΄Π΅Π»Π° (Umaru, Omame, 2020); 2) любоС количСство тСхнологичСских систСм, связанных с сотрудничСством, сообщСством, взаимодСйствиСм, Π° Ρ‚Π°ΠΊΠΆΠ΅ созданиСм ΠΈ ΠΎΠ±ΠΌΠ΅Π½ΠΎΠΌ ΠΊΠΎΠ½Ρ‚Π΅Π½Ρ‚ΠΎΠΌ Π² Ρ€Π΅Π°Π»ΡŒΠ½ΠΎΠΌ Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ (Reham, 2020). Π’Π°ΠΊΠΈΠΌ ΠΎΠ±Ρ€Π°Π·ΠΎΠΌ, ΠΌΠΎΠΆΠ½ΠΎ Π³ΠΎΠ²ΠΎΡ€ΠΈΡ‚ΡŒ ΠΎ Ρ‚ΠΎΠΌ, Ρ‡Ρ‚ΠΎ ΡΠΎΡ†ΠΈΠ°Π»ΡŒΠ½Ρ‹Π΅ сСти -это Π½ΠΎΠ²Ρ‹ΠΉ Π½Π°Π±ΠΎΡ€ тСхнологичСских инструмСнтов, ΠΏΠΎΠ·Π²ΠΎΠ»ΡΡŽΡ‰ΠΈΡ… осу-1 Π–ΠΈΠ·Π½ΡŒ ΠΎΠ½Π»Π°ΠΉΠ½: ΠΏΠΎΡ‚Ρ€Π΅Π±Π»Π΅Π½ΠΈΠ΅, пользованиС, развлСчСния : аналитичСский ΠΎΠ±Π·ΠΎΡ€ // Π’Π¦Π˜ΠžΠœ.…”
Section: Introductionunclassified
“…However, most of these studies only illuminated physical library Twitter use. There is a difference in how Twitter is used in different types of library settings (Alsuhaibani, 2018). Despite DLs growing in the past decade, they were often not a part of the overarching Twitter library and information science research.…”
Section: Introductionmentioning
confidence: 99%